2010
DOI: 10.2175/193864710798182826
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Approach for Modeling Sludge Reduction Technologies

Abstract: Sludge reduction technologies have gained popularity as solids handling and disposal become an increasingly costly portion of a wastewater treatment plant. The technologies are implemented within the liquid processes for waste activated sludge minimization, or as pre-treatment to anaerobic digestion to enhance digestion and reduce biosolids. Biological, chemical, and/or physical procedures are used and achieve varying level of success, but the underlying mechanisms are not well understood and modeled. The pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…A few research groups have proposed approaches for modeling WAS pretreatment technologies and an even fewer number have published stand-alone pretreatment models. Lei et al (2010) Lei et al (2010), the original plant-wide model was adjusted to fit the data measured after pretreatment implementation by increasing the anaerobic disintegration rate and transforming inert decay products to biodegradable COD. The authors demonstrated that the measured ammonia increase after digestion due to the HPTH pretreatment could only be explained by a complete degradation of decay products.…”
Section: Existing Pretreatment Modelsmentioning
confidence: 99%
“…A few research groups have proposed approaches for modeling WAS pretreatment technologies and an even fewer number have published stand-alone pretreatment models. Lei et al (2010) Lei et al (2010), the original plant-wide model was adjusted to fit the data measured after pretreatment implementation by increasing the anaerobic disintegration rate and transforming inert decay products to biodegradable COD. The authors demonstrated that the measured ammonia increase after digestion due to the HPTH pretreatment could only be explained by a complete degradation of decay products.…”
Section: Existing Pretreatment Modelsmentioning
confidence: 99%
“…A generally accepted means of characterizing and comparing the impact of pretreatment processes on these responses does not exist. A few research groups have presented approaches for modeling WAS pretreatment technologies (Lei et al, 2010;Phothilangka et al, 2008;Frigon and Isazadeh, 2010;Musser, 2009). However, in these studies, assumptions about the WAS COD fractionation were required because of the complex nature of the biomass.…”
Section: Introductionmentioning
confidence: 99%
“…The application of ASM2d-ADM1 modeling of digestion processes with sludge pre-treatment for improved digestibility was discussed Lei et al, 2010) (2010b) provided a consensus report on the state-of-the art, areas of uncertainty, and future needs for advancing the use of biofilm models in engineering design. A pilot-scale fixed-biofilm reactor (FBR) was established by Lin (2010) to treat textile wastewater to evaluate the feasibility of replacing conventional treatment processes that involve activated sludge and coagulation units.…”
mentioning
confidence: 99%